Local Government Units in Indonesia: Demographic Attributes and Differences in Financial Condition - Rusmin Rusmin; Emita W. Astami; Glennda Scully (Australasian Accounting, Business and Finance Journal, 2014)
This study examines the outcome of decentralisation reforms in Indonesia, focusing on the association between demographic characteristics and differences in the financial condition of local governments units. It investigates cross-sectional data pertaining to demographic characteristics and financial statements audited by the Supreme Audit Body of 419 Indonesian local government units for the fiscal year 2007. It utilises demographic attributes including scope of entity, location, tenure (date of entry), gender, human development index (HDI) and size of local governments to explain differences in the financial condition of Indonesia’s local government. Local government financial condition is proxied by quick ratio, debt ratio, services ratio, and ratio of local to total revenues. The results suggest that scope and location of local government units help explain all of the financial condition variables. The findings further infer that local government units domiciled in Java tend to report better financial conditions relative to those domiciled in other islands. Our results also show that local government units with greater female populations and higher HDI are more likely to have a local authority that (1) has better ability to finance their general services from their unrestricted net assets, and (2) has greater ability to earn more revenues from local sources. Finally, this study documents that the larger the population of a local government unit, the higher its liquidity position, the stronger its ability to funding general services, and the greater its possibility earning revenues from its local sources.
Keywords: Demographic attributes; local government; financial condition; Indonesia